A revised checklist of Cooperia nematodes (Trichostrogyloidea), common parasites of wild and domestic ruminants - Albrechtová M.; Langrová I.; Vadlejch J.; Špakulová M. (Helminthologia, 2020)
This review updates the current knowledge on the taxonomy of intestinal nematodes of the genus Cooperia parasitizing in wild and domestic ruminants. The emphasis is put on revision of 19 valid species belonging to the genus. This analysis focuses on main features of the genus Cooperia, including its geographic occurrence and the life cycle details. The most widespread congeners are Cooperia curticei, C. oncophora, C. pectinata, and C. punctata, having nearly worldwide distribution. The fifth species, referred by electronic databases from the European territory as Cooperia asamatiSpiridonov, 1985, is unveiled here originally as nomen nudum.